FANGIRLS, AFFECT AND STRATEGIES OF INCLUSION IN THE NEW GAMING PUBLIC - Ask, Kristine; Bang Svendsen, Stine H. (AoIR Selected Papers of Internet Research, 2014)
The masculine gendering of video games has proven persistent. Despite a dramatic increase in the number of female gamers women are still struggling for legitimate participation in gaming culture. This is particularly visible in the many game related communities and arenas that have emerged online -what may be referred to as the new gaming public. Here we can see that attempts to put women’s issues on the agenda has been met with an «extreme and virulent lashing out against those who are perceived as others, most notably women» (Salter & Blodgett, 2012, p. 402). The toxic reactions to feminist voices in game culture where hypermasculinity and harassment are pervasive (Braithwaite, 2013), prompts questions about where and how women can safely express their interest and appreciation for games. This paper looks at how games and game culture is constructed in one such new gaming public, namely the fan blogs on tumblr.